Wireless Access Policy for Electronic Communications Services (WAPECS): Collision between theory and practice - Mohamed El-Moghazi; Jason Whalley; James Irvine (International Telecommunications Society (ITS), 2014)
Fifty five years ago, Coase suggested in his seminal article 'The Federal Communications Commission' that spectrum assignments should be treated in a similar way to property rights where market forces allocate these flexible tradable rights to users with the highest valuations for it. While Coase's idea was appealing and gathered huge momentum in academia scene, the practice did not show much success. One of the first practical implementations was initiated in Europe in 2005 under the name 'Wireless Access Policy for Electronic Communication Services (WAPECS)'. WAPECS aimed at providing more flexibility in the European spectrum management framework by allowing using the spectrum on a technology and service neutral basis. At the international level, the European Conference of Postal and Telecommunications Administrations (CEPT) have been keen to introduce more flexibility at the international service allocation framework via different measures. The paper shows also that the international Radio Regulations (RR) can accommodate the WAPECS concept to a certain extent. Finally, the paper explains that the opposition from the other countries to the European attempts to introduce flexibility to the international service allocation framework is due to the potential implications at the national level.
Keywords: 330